Care Pathways in Persistent Orofacial Pain: Qualitative Evidence from the DEEP Study. (January 2017) - Breckons, M.; Bissett, S.M.; Exley, C.; Araujo-Soares, V.; Durham, J.
Persistent orofacial pain is relatively common and known to have an adverse effect on quality of life. Previous studies suggest that the current care pathway may be problematic, but it is not well understood which health services patients access and what their experience is. The aim of this study was to explore care pathways and their impact from the perspective of patients. Qualitative interviews were conducted with a maximum variation sample of patients recruited from primary (community based) and secondary (specialist hospital based) care in the United Kingdom. Questions focused on the stages in their pathway and the impact of the care that they had received. Interviews were digitally recorded and transcribed verbatim, and analysis followed principles of the constant comparative method. NVivo 10 was used to help organize and analyze data. Twenty-two patients were interviewed at baseline, and 18 took part in a second interview at 12 mo. Three main themes emerged from the data: the "fluidity of the care pathway, " in which patients described moving among health care providers in attempts to have their pain diagnosed and managed, occurring alongside a "failure to progress, " where despite multiple appointments, patients described frustration at delays in obtaining a diagnosis and effective treatment for their pain. Throughout their care pathways, patients described the "effects of unmanaged pain, " where the longer the pain went unmanaged, the greater its potential to negatively affect their lives. Findings of this study suggest that the current care pathway is inefficient and fails to meet patient needs. Future work needs to focus on working with stakeholder groups to redesign patient-centered care pathways. Knowledge Transfer Statement: Data from qualitative interviews conducted with patients with persistent orofacial pain suggest significant problems with the existing care pathway, consisting of delays to diagnosis, treatment, and referral. Patients describing their struggle to progress through the current care pathway highlighted the difficulties occurring while living with orofacial pain. This study suggests a need for a revised care pathway, which better meets the needs of people with persistent orofacial pain.